A proposal of a new material for greenhouses on the basis of numerical, optical, thermal and mechanical approaches. (30th November 2017) - Sfarra, Stefano; Perilli, Stefano; Ambrosini, Dario; Paoletti, Domenica; Nardi, Iole; de Rubeis, Tullio; Santulli, Carlo
Graphical abstract: Highlights: Endothermic events were discovered both in pure and modified HDPE samples. A pseudo-static matrix reconstruction algorithm applied to IRT data was used. Thermocouples monitored the temperature variation in time during the tensile tests. The UV optical transparency in the modified HDPE increased after the tensile test. Numerical and experimental temperature variations follow similar trends in time. Abstract: The use of recycled paper in HDPE (High Density PolyEthylene) matrix composites has recently been introduced as an interesting alternative to traditional recycling process for paper. HDPE is also used as double wall greenhouse glazing because panels are easy to install, UV stabilized, and affordable. These type of products must also be strong enough and durable in order to react under tensile loads provided by wind and harsh weather conditions. An interesting idea may be the insertion via injection moulding of chopped basalt and waste paper – i.e., two natural products – in pure HDPE samples. It completely follows the environmental sustainability concept centred on the triple " re ", i.e., re cycle, re use and re duce. The research presented herein starts with a Differential Scanning Calorimetry (DSC) inspection of pure HDPE and HDPE mixed with 5% by weight of waste paper plus 5% by weight of chopped basalt as fillers in order to obtain an insight related to the temperature at which possible thermal events (endothermic or exothermic) occur. The dog-bone samples were also inspected under UV conditions (380 nm) before and after tensile tests. The latter approach was simulated firstly by Comsol Multiphysics® computer program, and secondly recorded in real time via thermographic inspections. The temperature variation in a region of interest (ROI) selected at the centre of the samples was mapped in the time during the inspection by infrared thermography (IRT) method using a pseudo-static matrix reconstruction algorithm realized in Matlab® environment. Instead, the combined use of thermocouples aimed at emphasizing the knowledge of the heat transfer in the time due to the mechanical stress applied at the borders of the inspected samples. The aim was to understand whether modified HDPE can (or cannot) be a valid competitor of pure HDPE for the production of semi-transparent and robust panels.